Peran Perencanaan Strategi Dalam Memediasi Pengaruh Faktor Manajerial Terhadap Kinerja UMKM Handycraft Bantul - Meliala, Ferdinan Jurintha; Sabihaini; Widjanarko, Hendro (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
In the current era of development, competition in the business world is increasingly fierce and unavoidable, with the start of the Asian Economic Community (AEC) which should be able to increase the amount of exports but the number of exports of Bantul Regency has decreased for 2017 compared to 2015. This study aims to test hypotheses; (1) Effect of managerial factors on performance; (2) The influence of managerial factors on strategic planning; (3) The effect of strategic planning on performance; (4) The influence of managerial factors on MSME performance is mediated by strategic planning. This type of research is associative with data collection used is cluster random sampling from a sample of 94 units and then analyzed using descriptive statistical methods with partial least square (PLS). The method used for the validity test is the convergent validity test and composite reliability test to test reliability. The results and conclusions of this study are proven that all hypotheses have a positive and significant influence.